2000
DOI: 10.1103/physreve.62.303
|View full text |Cite
|
Sign up to set email alerts
|

Canonical solution of a system of long-range interacting rotators on a lattice

Abstract: The canonical partition function of a system of rotators (classical X-Y spins) on a lattice, coupled by terms decaying as the inverse of their distance to the power α, is analytically computed. It is also shown how to compute a rescaling function that allows to reduce the model, for any d-dimensional lattice and for any α < d, to the mean field (α = 0) model. PACS: 05.20.-y, 05.70.Ce, 05.10.-a

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
85
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 6 publications
10
85
0
Order By: Relevance
“…Besides confirming the scaling properties with α, they have also shown that the number of states is of order exp(N ). The exact solution of these models in the canonical ensemble has been obtained by Campa et al [43] and Vollmayr-Lee and Luijten [44]. The scaling of the magnetization and of the energy curve with the α-exponent has been exhibited in full detail.…”
Section: The Ising Model With 1/r α Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides confirming the scaling properties with α, they have also shown that the number of states is of order exp(N ). The exact solution of these models in the canonical ensemble has been obtained by Campa et al [43] and Vollmayr-Lee and Luijten [44]. The scaling of the magnetization and of the energy curve with the α-exponent has been exhibited in full detail.…”
Section: The Ising Model With 1/r α Interactionsmentioning
confidence: 99%
“…In all these cases the interaction is singular at shortrange. Interesting toy models (which generalize the HMF model) without a short distance singularity have been recently proposed [41,42,43,44]. In these latter models, XY spins are put on a lattice and interact through a slowly decreasing non integrable 1/r α law (α < d).…”
Section: The Ising Model With 1/r α Interactionsmentioning
confidence: 99%
“…Next, we consider the system at K < 1=2. This case has been studied in the context of discrete XY models [36][37][38] and was shown to have a phase transition in the limit that the coupling vanishes as a power of the system size, which in our case is ¼ 1=T; i.e., there is a critical value for ð Þ 1À2K . Hence, at T ¼ 0 the system is fully ordered and hcosX i ¼ 1.…”
mentioning
confidence: 99%
“…Within the class of long-range interacting systems, classical spin models, widely investigated during the last years [7], are the most easy-to-handle both from the analytical and the numerical point of view. Within such class of systems, (to be more precise, a class of anisotropic Heisenberg models) the existence of a threshold of disconnection in the energy surface has been demonstrated [1] for an interparticle interaction with infinite range.…”
Section: Introductionmentioning
confidence: 99%